Một cách tiếp cận sử thi Tây Nguyên - Phạm, Văn Hóa (Trường Đại học Đà Lạt, 2012)
Ever, epic played a very important in the cultural life of the Tay Nguyen. To collect and study in the Tay Nguyen epic decades has continuously conducted and developed. Epic of Tay Nguyen was the object of attention fo many generations of scientists and achievements in the field of study is worth noting. Researchers and teaching epic of Tay Nguyen was not simply looking to receive elements concentrated language of the work that attention to factors other non-words, the conditions exist, took initiative in the life culture of it, put the work of implementaion in relation to folklore.